Exclusive Breastfeeding and Its Implications for Infant and Maternal Health, Knowledge, and Socioeconomic Well-being - Aswita Amir; Rudy Hartono; Ronny Horax; Adriyani Adam (Poltekkes Kemenkes Palu, 2025)
This systematic review synthesized recent evidence on the impact of exclusive breastfeeding (EBF) on infant and maternal health, maternal knowledge, and family socioeconomic conditions. Following PRISMA 2020 guidelines, we conducted systematic searches in PubMed, ScienceDirect, JSTOR, and Google Scholar. From 500 identified records, 10 studies published between 2020 and 2025 met the inclusion criteria. Meta-analysis showed that EBF reduced gastrointestinal infection risk in infants by 45% (OR = 0.55; 95% CI: 0.45–0.67), increased cognitive development scores by 0.35 SD compared to formula-fed infants, and reduced maternal breast cancer risk by 25%. Narrative synthesis indicated significant economic savings at the household level through reduced formula purchases and healthcare utilization. These findings underscored the importance of maternal knowledge, family support, and breastfeeding-friendly workplace policies in sustaining EBF. The review provided critical implications for global and national health policies to promote and protect EBF practices.